Strategi Optimalisasi Tata Letak Gudang dalam Meningkatkan Efisiensi Arus Material: Studi Kasus pada Gudang Distribusi Retail - Dewa Ayu Indiana Ida Loemongga Sandopart (CV. Global Cendekia Inti, 2026)
This study aims to formulate warehouse layout optimization strategies to improve material flow efficiency in retail distribution warehouses. Using a qualitative approach with a case study method, this research was conducted at a fast-moving consumer goods (FMCG) distribution warehouse in the Jakarta area. Data collection was carried out through participatory observation, semi-structured interviews with 12 participants (managers, supervisors, operational staff, pickers, checkers, and inventory control staff), and document studies. Data analysis employed the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the existing layout implements a random storage system without classification based on movement frequency, resulting in material handling distances reaching 1,450 meters per cycle (31% above industry standard), picking time of 4.2 minutes per line item, space utilization of only 68%, and a shipping error rate of 3.8%. Analysis shows that 15% of SKUs account for 78% of picking activity. The novelty of this research lies in the integration of class-based storage methods based on FSN (Fast, Slow, Non-moving) analysis with product association identification, as well as the recognition of non-physical factors (equipment limitations, WMS rigidity, informal worker adaptive strategies) as determinants of implementation success. The formulated optimization strategy has the potential to reduce material handling distances by 40-50%, reduce picking time by 30-35%, and reduce material handling operational costs by 25-30%. This research contributes to the development of a contextual and holistic layout optimization framework for retail distribution warehouse.